PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PREDIKTABILITAS LABA PADA PERUSAHAAN YANG TERDAFTAR DALAM LQ45 TAHUN 2010 SAMPAI 2014 - Nathania Nathania; Juniarti Juniarti (Business Accounting Review, 2016)
The objective of this research was to identify the influence of Corporate Social Responsibility to predictability earning in listed companies in LQ45 in 2010 until 2014. These sample were taken from 64 samples. The result showed that corporate social responsibility had positive affect to predictability earning. And control variable, firm size had positive affect to predictability earning and leverage had no affect to predictability earning.